Adapting implementation strategies: a case study of how to support implementation of healthy canteen policies. (December 2019) - Yoong, S.L.; Nathan, N.; Reilly, K.; Sutherland, R.; Straus, S.; Barnes, C.; Grady, A.; Wolfenden, L.
Abstract: Objectives: Although evidence-based interventions (EBIs) and effective strategies to implement them exist, they cannot be used by policy makers and practitioners if they do not align with end users' needs. As such, adaptations to EBIs and implementation approaches are likely to occur to increase 'fit' with end users' capacity. This article describes an approach undertaken by a population health service delivery unit in one Australian state to develop an adapted implementation strategy to support the implementation of the mandatory healthy canteen policy (EBI) to all schools located in the service delivery region. Study design: This is a case study of adapting an intervention to improve implementation of the healthy canteen policy. Methods and results: This is a six-step pragmatic, empirically driven approach. The steps include (i) adapt, where appropriate, the EBI to facilitate implementation; (ii) identify end users' capacity for implementation; (iii) identify opportunities to adapt the implementation interventions while preserving meaningful intervention impact; (iv) undertake program adaptation; (v) develop training and resources to support delivery of implementation strategies and; (vi) evaluate the adapted intervention. This article describes the application of these steps by the authors to develop an adapted support strategy consistent with end users' needs. Conclusions: This study provides some guidance on how to adapt implementation support approaches particularly when EBIs cannot be adapted. Future empirical research providing guidance on making practical adaptation decisions are needed. Highlights: Adaptation regularly occurs to public health programs to increase the 'fit'. Current evidence provides little guidance on adapting implementation approaches. This study describes our experience adapting implementation approach.